Training Psychiatric Patients for Community Living Carl A. Aveni and Dennis Upper. - Aveni, Carl A. (Distributed by ERIC Clearinghouse, 1976)
In this paper, the authors report that in many of the cases they have treated, the living situations and/or environments to which patients were returning upon discharge, were not suitable for either maintaining, or improving upon, the gains achieved while hospitalized. As a result, a community residence training program, based upon a behavioral principles model, was developed and is described. The program targets those patients who appear to have the potential to learn the skills necessary for self-care, with the focus centering around the principle of Successive Approximations. Consistent with this model, and in an effort to establish appropriate expectations during the training process, the program was divided into three separate developmental areas: (1) self-maintenance skills, (2) social-interpersonal skills, and (3) work skills. After four years of training programs and placing several groups, pairs, and even individual patients into the community, continued follow-up reports indicate the success of the program. The authors feel that the continuity of residence in the community for the period of time the original group maintained (ranging from 13 months to four years) as well as the need for less support, is significant evidence that this program works. (Author/YJ)